Food Packaging Materials : Testing & Quality Assurance. - Singh, Preeti; Wani, Ali Abas; Langowski, Horst-Christian (CRC Press, 2017)
"This book is arguably the first one focusing on packaging material testing and quality assurance. It provides information to help food scientists, polymer chemists, and packaging technologists find practical solutions to packaging defects and to develop innovative packaging materials for food products. Knowledge of packaging material testing procedures is extremely useful in the development of new packaging materials. Unique among books on packaging, this reference focuses on basic and practical approaches for testing packaging materials."--Provided by publisher.